Evaluating the efficacy of vacuum constrictive device and causes of its failure in impotent patients - Khayyamfar, Feraidoon; Forootan, Seyed Kazem; Ghasemi, Hassan; Miri, Seyed Roohollah; Farhadi, Ehsan (Urology Journal, 2014)
Abstract PURPOSE: This study evaluates the efficacy of Vacuum constrictive device (VCD) and the reasons for its failure. Materials and Methods: In this cross-sectional study, 1500 men with organic erectile dysfunction(ED) were enrolled from July 2003 to July 2010. The treatment efficacy was analyzed using International Index of Erectile Function (IIEF) and questioning patient’s partner regarding the man’s ability to perform vaginal penetration (APVP). The patient’s spouses, who responded negatively to APVP, were evaluated by a midwife for virginity, vaginal atrophy and abstained sex. Results: Totally 1310 (87.4%) patients attained full erection at first training session, remaining188 (12.6%) were able to have full erection one week after practicing with VCD, 1419 (94.6%)were able to have successful intercourse and responded positively to APVP, 81 (5.4%) were unable to have intercourse as stated by their wife’s (negative response to APVP) that in 43 (53%),30 (37%), and 8 (9.8%) cases the causes of failures were their wife’s virginity, sex abstinence, and senile vaginal atrophy, respectively. Regarding erectile issue of IIEF scores in patient’s responded positive to APVP there were significant improvement from the scores of 9.3 ± 3.0 to 27.5 ± 5.0 after treatment (P < .05). Conclusion: With proper training and appropriate devices, VCD could induce sufficient erection in all patients. VCD in patients with virgin wife is ineffective, and female factors affect on success rate in VCD therapy.